MicroRNA miR396 and RDR6 synergistically regulate leaf development - Mecchia, Martin Alejandro (2013)
The miroRNA (miRNA) miR396 regulates Growth-Regulating Factors (GRFs), a plant specific family of transcription factors. Overexpression of miR396 causes a decrease in the GRFs that has been shown to affect cell proliferation in the meristem and developing leaves. To bring further insights into the function of the miR396 regulatory network we performed a mutant enhancer screen of a stable Arabidopsis transgenic line expressing 35S:miR396b, which has a reduction in leaf size. From this screen we recovered several mutants enhancing this phenotype and displaying organs with lotus- or needle-like shape. Analysis of these plants revealed mutations in as2 and rdr6. While 35S:miR396b in an as2 context generated organs with lotus-like shape, the overexpression of the miRNA in an rdr6 mutant background caused more important developmental defects, including pin-like organs and lobed leaves. Combination of miR396 overexpressors, and rdr6 and as2 mutants show additional organ defects, suggesting that the three pathways act in concert. Genetic interactions during leaf development were observed in a similar way between miR396 overexpression and mutants in RDR6, SGS3 or AGO7, which are known to participate in trans-acting siRNA (ta-siRNA) biogenesis. Furthermore, we found that miR396 can cause lotus- and pin-like organs per se, once a certain expression threshold is overcome. In good agreement, mutants accumulating high levels of TCP4, which induces miR396, interacted with the AS1/AS2 pathway to generate lotus-like organs. The results indicate that the miR396 regulatory network and the ta-siRNA biogenesis pathway synergistically interact during leaf development and morphogenesis.